Potensi Destinasi Wisata Geopark Gunungsewu Segmen Geoarea Wonogiri - Muhammad Irham; Endrawati Fatimah; Anindita Ramadhani (Jurnal Lingkungan dan Kota, 2021)
Geoarea Wonogiri has many tourist objects and a large area, it needs integrated management, therefore it is necessary to study the potential of tourism, so this research aims to analyze the potential of these locations, therefore an analysis of the potential attractiveness in each district is needed. The research method used is Qualitative research after that used the analysis of scoring techniques. Based on the results of this study, Pracimantoro District is the most potential for the Development of Tourist Destinations in Geoarea Wonogiri because it has the advantage of potential analysis based on the 4A aspect (attraction, amenities, accesibitily, ancillary).